Improved Research and Experience Sharing of the Ureteroscope Examination Experimental Model in Mini-pigs - Leng, Xiaoping; Chen, Gang (Journal of Contemporary Medical Practice, 2024)
Objectives: Currently, there is limited literature available on animal experimental models of pigs, specifically in regards to experimental models of ureteroscopy. Materials and Methods: Seven healthy mini-pigs weighing 25kg-30kg, with comparable age, size, and living environment, were selected for the study. Before surgery, intravenous propofol 20 ml was given for general anesthesia. The pig was placed in a supine position, with fixed limbs and separated labia. After disinfection and using a sterile cave towel, the ureteroscope was placed in the urine germinal vestibule, and the external urethral opening was expanded under perfusion fluid. The urethral microscope smoothly entered the urethra, and the ureter opening was identified at 5 o'clock and 7 o'clock. The zebra guide wire was placed into the left ureter, and the ureteroscope was successfully placed into the left ureter. The 5F double J tube was placed in the ureter, and its end remained in the bladder. The ureteroscope was re-entered to check the right ureter opening and another 5F double J tube was placed in the right kidney and down in the bladder. The operation was successfully completed without any abnormalities found. Results: The surgical time for establishing an experimental model in 7 mini-pigs varied, with the first pig taking 81 minutes due to lack of experience in water pressure control, search and identification of openings, and re-entering the ureteroscope. The remaining 6 mini-pigs had reduced surgical time, with the last two taking 21 and 19 minutes respectively. The 6 mini-pigs survived normally after surgery. Postoperative X-ray showed bilateral ureteral stents in good position. The animals were observed for breathing, waking up, and normal activities without abnormalities. Conclusions: An experimental model of improved mini-pigs for ureteral stent placement has been established using a new method. The assistant clamps the labia to reduce fluid loss, maintains perfusion pressure, and retains a guide wire in the bladder during stent placement on one side. The ureteroscope is guided by two guide wires, significantly reducing operation and anesthesia time, minimizing animal health damage, and lowering mortality rates. This method has reference and promotional significance for future studies.